2003
DOI: 10.1128/jvi.77.23.12543-12551.2003
|View full text |Cite
|
Sign up to set email alerts
|

Role for Influenza Virus Envelope Cholesterol in Virus Entry and Infection

Abstract: Enveloped viruses are highly dependent on their lipid envelopes for entry into and infection of host cells. Here, we have examined the role of cholesterol in the virus envelope, using methyl-␤-cyclodextrin depletion. Pretreatment of virions with methyl-␤-cyclodextrin efficiently depleted envelope cholesterol from influenza virus and significantly reduced virus infectivity in a dose-dependent manner. A nonenveloped virus, simian virus 40, was not affected by methyl-␤-cyclodextrin treatment. In the case of influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
188
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(214 citation statements)
references
References 50 publications
(58 reference statements)
15
188
1
2
Order By: Relevance
“…Influenza virus envelope cholesterol also plays a role in virus entry and infection 40 . It has been hypothesized that influenza hemagglutinin concentrates by partitioning into lipid raft microdomains, thus reaching densities needed for the hemagglutinin-mediated fusion of virus infection 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Influenza virus envelope cholesterol also plays a role in virus entry and infection 40 . It has been hypothesized that influenza hemagglutinin concentrates by partitioning into lipid raft microdomains, thus reaching densities needed for the hemagglutinin-mediated fusion of virus infection 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Many papers suggested that lipid rafts were involved in various cellular processes such as signal transduction, apoptosis or protein sorting [20,21]. They have also been shown to play a role in HIV or influenza viruses infection processes [22][23][24].…”
Section: Lipid Microdomains and Membrane Raftsmentioning
confidence: 99%
“…Many papers suggested that lipid rafts were involved in various cellular processes such as signal transduction, apoptosis or protein sorting [20,21]. They have also been shown to play a role in HIV or influenza viruses infection processes [22][23][24].Model membrane experiments have shown that liquidordered microdomains in fluid membranes can exist and that proteins can preferentially segregate into the fluid or the ordered phase domain [25,26]. However, biological membranes are much more complex than synthetic membranes, and the presence of lipid rafts in intact cells still remains to be proved.…”
mentioning
confidence: 99%
“…As commented before, specific lipids located in the viral particles can also play a role on viral entry of enveloped viruses [8], including 'those located in' lipid rafts [49][50][51]. Vaccinia virus provides another example of the relationships between lipids located on the viral particle and viral entry.…”
Section: Lipids and Viral Internalizationmentioning
confidence: 99%
“…Lipid rafts have been related to the entry of a number of viruses, for example the coronavirus severe acute respiratory syndrome (SARS), murine leukemia virus, herpes simplex virus, Japanese encephalitis virus, SV40, and echovirus 1 [34,[43][44][45][46][47][48]. In addition, some viruses require cholesterol-enriched microdomains in the viral membrane for efficient virus entry, for example influenza virus A, human herpes virus 6, and Canine distemper virus [49][50][51]. On the other hand, some viruses that enter into the cells using mechanisms independent of lipid rafts require cholesterol for an efficient internalization.…”
Section: Lipids and Viral Internalizationmentioning
confidence: 99%